Prediksi dan Identifikasi Struktur Protein EGFR Kanker Paru dengan Mutasi Titik L718Q/T790M Secara Pemodelan Homologi In Silico - Dwi Syah Fitra Ramadhan; Daryono H. Tjahjono (Jurnal Sains dan Kesehatan, 2020)
EGFR receptors play an important role in the growth of cancer cells, and these receptors have undergone various types of mutations. At this time, the effect of the L718Q / T790M point mutation on the EGFR receptor is not known, therefore the aim of this study is to predict the EGFR structure with the L718Q / T790M point mutation using in silico homology modeling. The mutant protein was successfully modeled using SWISS-Model expasy webserver and showed good evaluation results after the protein was minimized as indicated by the results of the Ramachandran outlier score of 0%, clashscore 0.98, and MolProbity 1.15. Identification of the active site of the mutant protein shows a conformational change of the active site that causes a steric collision between the inhibitor group and the amino acid side chain of the mutant protein. Keywords: EGFR, mutation, homology modeling, in silico.